2021
DOI: 10.15376/biores.16.3.4876-4890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of press-forming parameters on the dimensional stability of paperboard trays

Abstract: The dimensional stability of press-formed paperboard trays was investigated during heating and cooling of trays packed with oatmeal. Female mold tool temperature, dwell time, pressing force, and blank holding force were altered in the press-forming of the trays to observe their impacts on the dimensional stability. Dimensional measurements of the trays showed reduced tray width, and the trays exhibited distortions on the tray flange and outer wall. The results showed smaller effects on the tray length, paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…The overall quality of sealed paperboard trays has been linked to the utilised heatsealing and press-forming parameters (Leminen et al 2015a(Leminen et al , 2017. A lower blank holding force in the press-forming process produced more durable paperboard trays for use in food processing compared to previous results (Niini et al 2020a), whereas a higher blank holding force improved the quality of heat-sealed paperboard trays. (Leminen et al 2015a) In a previous study it was found that drying the trays, as compared to preconditioning, improved the durability of press-formed paperboard trays used for food processing (Niini et al 2020b).…”
Section: Introductioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The overall quality of sealed paperboard trays has been linked to the utilised heatsealing and press-forming parameters (Leminen et al 2015a(Leminen et al , 2017. A lower blank holding force in the press-forming process produced more durable paperboard trays for use in food processing compared to previous results (Niini et al 2020a), whereas a higher blank holding force improved the quality of heat-sealed paperboard trays. (Leminen et al 2015a) In a previous study it was found that drying the trays, as compared to preconditioning, improved the durability of press-formed paperboard trays used for food processing (Niini et al 2020b).…”
Section: Introductioncontrasting
confidence: 57%
“…In a previous study, the use of a higher forming tool temperature (180 °C) in the press-forming process of GN1/4 paperboard trays resulted in a smaller difference between the measured widths and the standard tray widths (Niini et al 2020a). The implicated effect from the weight of oatmeal on the width of the tray was due to the tray being loaded with raw oatmeal before the initial dimension measurements; the load of the oatmeal thereby being apparent in the measured tray width.…”
Section: Fig 2 Impact Of Tray Flange Distortion On Tray Widthmentioning
confidence: 84%
“…The change in fiber structure can be characterized by subjecting the samples to selected physical and visual analyses. The dimensional stability of press-formed cardboard trays during heating and cooling was investigated in Niini et al (2021). The effect of heat input during folding on paperboard tray stiffness based on compression and torsion tests was evaluated in Niini et al (2022).…”
Section: Introductionmentioning
confidence: 99%